The scope of the competence of the constitutional judiciary to monitoring constitutional amendments - Rasoul, Roman (Humanities Journal of University of Zakho, 2021)
This paper tackles a comparative analytical study on the constitutional jurisdiction concerning monitoring constitutional reforms (amendments) which expands the aspect of the monitoring. Thus, it affirms that the unconstitutional amendments are considered the most risky defects that negatively affect the constitutional amendments. This study also shows the theoretical explanation of the significance of the constitutional and unconstitutional amendments. Furthermore, it covers jurisdiction courts that are specialized to monitor constitutional reforms (amendments) when there is an explicit provision in the constitution and how the jurisdiction courts will be specialized to monitor those amendments when there is no explicit provision in the constitution. It further discusses the case how the jurisdiction courts dealing with monitoring constitutional reforms (amendments) objectively when there are objective limitations and when there are not any. This is to clarify whether these limitations are implicit or not. In the end, the study concludes the results and recommendations.